Developing Managers as Learners and Researchers: Using Action Learning and Action Research - Joseph A. Raelin; David Coghlan (Journal of Management Education, 2006)
This article takes the view that formal educational programs often miss opportunities to use the rich experiences of working managers to produce both learning and knowledge. Two alternative pedagogical approaches, action learning and action research, are proposed as contributing to management education by their respective capabilities to generate practical learning and produce actionable knowledge. These approaches are compared with one another and with conventional classroom methodology using a new framework based on voice, level, form, and time.
Keywords: M10; M12; M53; D23; I21; J24; 650; Action learning; Action research; Actionable knowledge; Management education; Reflection; Management development